Global sourcing, firm size and export survival - Roger Bandick (Kiel Institute for the World Economy (IfW), 2019)
This paper investigates how firm size and global sourcing affect the export surviving probabilities. By using data on export and import transactions disaggregated by destination/origin for the entire Danish manufacturing firms between the periods 1995-2006, the author is able to classify the firms into different size categories and to observe whether they continue or cease to export. Moreover, he is able to define whether the firms source intermediate inputs from high- or low-wage counties. The results, after controlling for the endogeneity of the international sourcing decision by using IV and matching approach, indicate that firm size is positively correlated with the likelihood of continuing to export. Moreover, for small and medium size firms, global sourcing seems also to increase the probability of staying in the export market but only if they source from high- wage countries. However, sourcing inputs from abroad, no matter if it is from high- or low-wage countries, do not seem to significantly affect the export surviving probabilities for larger firms.
Keywords: F16; F23; J24; L25; 330; global sourcing; firm size; export; IV; matching; cloglog